New Zealand - Fox, Mary Virginia (Chicago : Childrens Press, 1991)
Introduces New Zealand, first populated by the Maori, who named the land mass "Land of the Long White Cloud.".
Includes index.
Wilson's Children.
Wilson's Junior High School.
7.1
4-6
5-8
Keywords: New Zealand -- Juvenile literature; New Zealand; New Zealand